2020
DOI: 10.1101/2020.02.18.953042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Live cell imaging of the hyperthermophilic archaeonSulfolobus acidocaldariusidentifies complementary roles for two ESCRTIII homologues in ensuring a robust and symmetric cell division

Abstract: Live-cell imaging has revolutionized our understanding of dynamic cellular processes in bacteria and eukaryotes. While similar techniques have recently been applied to the study of halophilic archaea, our ability to explore the cell biology of thermophilic archaea is limited, due to the technical challenges of imaging at high temperatures. Here, we report the construction of the Sulfoscope, a heated chamber that enables live-cell imaging on an inverted fluorescent microscope. Using this system combined with th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…The action of CdvC may then remodel the CdvB1 filaments whereupon the membrane shrinks, while CdvB2 keeps the ring in place. This idea is in line with previous findings (11) where mutants lacking CdvB1 were less able to perform the fission of the membrane, indicating its role in membrane deformation, whereas mutants without CdvB2 would lead to asymmetric divisions, suggesting its guiding role.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The action of CdvC may then remodel the CdvB1 filaments whereupon the membrane shrinks, while CdvB2 keeps the ring in place. This idea is in line with previous findings (11) where mutants lacking CdvB1 were less able to perform the fission of the membrane, indicating its role in membrane deformation, whereas mutants without CdvB2 would lead to asymmetric divisions, suggesting its guiding role.…”
Section: Discussionsupporting
confidence: 92%
“…It was shown that Sulfolobus cells lacking CdvB were unable to grow, while cells lacking the CdvB paralogs were still viable, albeit with a lower growth rate or aberrant daughter cells (10), and therefore the CdvB1-3 paralogs were deemed non-essential for cell division. Recently however, developments in hightemperature microscopy techniques (11,12) together with high-resolution imaging of fixed cells (13) shed valuable light onto how the CdvB paralogs participate in the cell division. It was shown that CdvB1 and B2 are recruited to the CdvB ring right before the cytokinesis, whereupon CdvB disappears from the membrane, while CdvB1 and CdvB2 carry out the deformation of the membrane needed for the division of the cell (11,13).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The flexibility of our device in terms of programming near-arbitrary temperature dynamics is also unmatched. While other modified devices have recently been constructed to allow for imaging at extreme temperatures [ 34 , 35 ], these instruments are more expensive than SiCTeC, highly customized, and limited to fluorescence imaging. Our device is entirely compatible with both brightfield and fluorescence imaging, which can be utilized to study protein localization and expression changes during temperature shifts as long as the temperature dependence of fluorescence is accounted for [ 36 ].…”
Section: Discussionmentioning
confidence: 99%